ASSESSING THE BENEFITS THAT COMMUNITY PHARMACIES CAN HAVE ON CHILDHOOD ASTHMA OUTCOMES. Issue 9 (17th August 2016) - Lilley, Andrew
Abstract : Introduction: The local Clinical Commissioning Group has funded an innovative one-year pilot project to assess the value of providing specialist paediatric pharmacist and physiotherapist support direct to families and health care professionals (GP's, community pharmacists, practice nurses etc.) regarding asthma in the primary care setting. Community pharmacies are the one service that asthmatic children come in contact with in order to pick up their medications it was decided to encourage staff to provide interventions at the point of collection. Methods: 22 large chain, small chain and independent community pharmacy branches were included in the pilot (out of 152 within CCG area) with a total of 31 pharmacists and 67 assistants trained to provide the service. The plan was to provide 'back to basics' leaflets on collection of prescription to help improve education on the medications being used; provide inhaler technique counselling on the collection of all prescriptions for children; encourage pharmacist's to perform medicines use reviews and the new medicines service in asthmatic children of high school age (for which they could collect the standard NHS fee). In order to assess the benefits of this, the pharmacist or assistant would first perform the standard asthma control test, marked out of 25 with the parent/patient completing an online version one month later to assess any improvement in symptom management. In order to trace the number of MURs, NMS, inhaler counselling sessions and leaflets given out a tally chart was completed each month by the branches involved. Results: Unfortunately of the 22 branches that signed up to the pilot only 15 returned tally charts to the team. Over a six month period 23 MUR's, 3 NMS and 32 inhaler technique sessions were performed with 67 leaflets distributed. Of a possible 55 asthma control tests (MURs and inhaler technique counselling sessions) only 23 patients completed the four week post intervention online form. Of those completed the average asthma control test score increased by 7 points (30% increase). In particular feedback from the pharmacists involved was that the inhaler counselling sessions were of particular benefit to parents/patients. Feedback from the pharmacy teams in general was positive with many stating it was good to be more involved in the care of children's conditions; however many stated in order for the service to roll out to a wider audience the scheme would have to provide a financial incentive for the large chains to take part. Conclusions: It is clear that interventions performed by the community pharmacy teams can help improve symptom control in asthmatic children. In particular ensuring patients are using their medications correctly appears to be key to symptom control. Encouraging pharmacists to provide child friendly MURs should be investigated further to prove the benefit of this service further. It should be noted that ensuring patients are using their medications correctly is already part of the essential service contract for pharmacies.